IDENTITAS GENDER DAN SEKSUAL SEBAGAI PERSONAL BRANDING PADA KONTEN TIKTOK LUCINTA LUNA - Joan Natasya Lambe; Vega Ulfie Rahmawati (Universitas Prof. Dr. Moestopo (Beragama), 2021)
In this technological era, media plays an important role in building personal branding. Not only companies, but individuals also need strong personal branding to get people's attention. Lucinta Luna is one of the celebrities who use their gender and sexual identity to make content called